IMPLEMENTING A CHILD-FRIENDLY PESANTREN CURRICULUM AN ETHNOGRAPHIC STUDY ON LIFE SKILLS DEVELOPMENT AT AL-MUSYARROFAH ISLAMIC BOARDING SCHOOL JAKARTA - Fauzih, Ahmad (Cendikia: Jurnal Pendidikan dan Pengajaran, 2024)
This study examines the implementation of a child-friendly curriculum at Al-Musyarrofah Islamic Boarding School, Jakarta, focusing on life skills development. In an era demanding well-rounded individuals, pesantren must go beyond religious knowledge to equip students with practical life skills. This qualitative study employs ethnographic methods, utilizing observations, interviews with stakeholders (teachers, students, leaders), and document analysis. Findings reveal successful integration of life skills education into Al-Musyarrofah's curriculum. The school emphasizes a balanced approach, recognizing religious instruction as one component of a holistic education. Teachers and students alike hold high expectations for the child-friendly curriculum, believing it enhances the learning experience and fosters crucial life skills. This includes fostering critical thinking, effective communication, problem-solving, and emotional intelligence, ultimately nurturing socially responsible and resilient individuals. The study recommends continuous professional development for educators, curriculum evaluation and adaptation, enhanced parent and community collaboration, and technology integration for program improvement.